Synthesis and Characterize Geopolymer as Erosion Mitigation for Seawater Application - Rosli, Siti Noriayana (Universiti Teknologi PETRONAS, 2016)
The discovery of a new class of inorganic materials, Geopolymer has been expanding in many areas whereby previously, it is only used for the production of cement and concrete. As we know, the cost of corrosion by seawater, aqueous corrosion, has been increased year upon year and corrosion control is needed in order to reduce the wasted materials, money, and energy. An alternative to Ordinary Portland Cement (OPC) has been developed in order to reduce CO2 emission to the environment as well as possess high durability in seawater, called fly ash based Geopolymer. Fly Ash is several examples of a source that has been used for the production of Geopolymer because of its low cost, environmentally friendly, and superior end products. This research present result of the durability of Fly Ash based Geopolymer in a seawater environment. In this project, different types of alkali activator, Sodium Hydroxide (NaOH) and Potassium Hydroxide (KOH) ratio will be tested with fixed concentration, curing time and temperature. Its durability against seawater environment also will be observed.